The ILRI Graduate Fellows Programme: A case study of impact (1978-1997) - Eley, R.; Ibrahim H.; Hambly Odame, Helen; Demeke, M.; Smalley, M.E. (Emerald Publishing Limited, 2003)
The paper explores the extent to which degree-based postgraduate training programmes contribute to the development of individual skills and careers in agricultural science as well as towards institutional capacity for national agricultural research in Africa. In the case of the International Livestock Research Institute's Graduate Fellowship Programme it was concluded that advanced agricultural science training in Africa provides a vital process of human and institutional development. The results of this study indicate the success of degree-based training in terms of achieving improved gender equity, rapid employment, and a high rate of return to the country of origin. These results-stand out against the "brain drain" commonly associated with capacity building in national agricultural research systems (NARS). The paper recommends strategies to be adopted by ILRI and its partners for future degree training and capacity building in sub-Saharan Africa.